Descriptive metadata for the newspaper clipping images of the U.P. Institute of Library and Information Science - Corros, Sarah H. (2003)
In order to make newspaper paper clipping images available and more accessible to the users, human intervention is needed to make intelligent image searching possible. This can be done by supplying the applicable metadata to the images. Two main standards are used as tools to determine the applicable metadata for the newspaper clipping image collection. The study focuses on the descriptive concept of metadata standards using Dublin Core. For description, the preliminary framework standard used in MARC21 because it has been used commonly used by librarians for descriptive cataloging. The content standard used is the AACR2r. The decision that Dublin Core is to be used for the final element set is based on the assumption that U.P. will soon be changing its operating system. Dublin Core can be written in HTML which is a universal mark-up language that can be read by any operating system.